De gentes anónimas y archivos nominales; una experiencia de integración entre análisis estadístico y prosopográfico - Samper K., Mario (1994)
First, the author offers a brief critical review of Costa Rican historical research methods in recent times, focusing primarily on quantitative vs. qualitative approaches. He then presents and assesses the experience of a specific research project at the Centro de Investigaciones Históricas of University of Costa Rica. The tile of that project was “Transformation of 1927 population census in a nominal data base”.